Assisted Soft Tissue Mobilization on Neck Disability in Patients with Upper Trapezius Trigger Points: A Quasi-Experimental Study: Assisted Soft Tissue Mobilization for Neck Disability in Upper Trapezius Trigger Points - Ahmed, Waqas; Asif, Muhammad; Mehmood, Nasir; Chandran, Suriyakala Perumal; Alam, Muhammad Shahzaib (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2026)
Myofascial trigger points in the upper trapezius are a common trigger of mechanical neck pain that is often associated with functional impairment assessed through the NDI. IASTM is universally used in the treatment of myofascial dysfunction; nevertheless, the literature on its role in disability outcome in clinical practice is scarce. Objectives: To assess the utility of an IASTM-based protocol in terms of NDI in trigger point patients of the upper trapezius compared with traditional physiotherapy. Methods: A non-randomized controlled quasi-experimental study was conducted, participants were recruited and not randomly assigned to either Group A (IASTM; n=25) or Group B (conventional physiotherapy; n=25). Group A (IASTM; n=25) and Group B (conventional physiotherapy; n=25) were randomly allocated 50 participants who had active upper trapezius trigger points lasting 3 months or more, of neck pain, which were determined using G*Power 3.1. The assessment of NDI was conducted at baseline and also at the end of the intervention period. Between-group comparisons were done with a significant level of p less than 0.05. Results: The groups had no differences in baseline NDI scores (Group A: 31.28 ± 5.09; Group B: 30.96 ± 5.32; p=0.82). Group A experienced a much lesser degree of disability than Group B (9.04 + 4.03 vs 20.12 + 4.64; p<0.001). Group A (mean= 22.24points) showed a higher reduction in NDI compared to Group B (mean= 10.84 points). Conclusions: A program of IASTM led to much better neck-related disability (NDI) than traditional physiotherapy in the patients who showed upper trapezius trigger points.